2020
DOI: 10.1002/advs.202003468
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol in the Viral Membrane is a Molecular Switch Governing HIV‐1 Env Clustering

Abstract: HIV‐1 entry requires the redistribution of envelope glycoproteins (Env) into a cluster and the presence of cholesterol (chol) in the viral membrane. However, the molecular mechanisms underlying the specific role of chol in infectivity and the driving force behind Env clustering remain unknown. Here, gp41 is demonstrated to directly interact with chol in the viral membrane via residues 751–854 in the cytoplasmic tail (CT751–854). Super‐resolution stimulated emission depletion (STED) nanoscopy analysis of Env di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…In addition, the entry of HIV-1 requires not only envelope glycoproteins to be redistributed into clusters but also cholesterol in the viral membrane. A residue in the cytoplasmic tail of gp41 directly interacts with cholesterol in the viral cell membrane 47 . There is evidence that the C-terminal of the spike's cytoplasmic tail of SARS-CoV-2 is the key to retention of membrane-mediated spike in the endoplasmic reticulum-Golgi intermediate compartment (ERGIC) 48 .…”
Section: Cholesterol Affects Susceptibility By Influencing the Process Of Membrane Fusionmentioning
confidence: 99%
“…In addition, the entry of HIV-1 requires not only envelope glycoproteins to be redistributed into clusters but also cholesterol in the viral membrane. A residue in the cytoplasmic tail of gp41 directly interacts with cholesterol in the viral cell membrane 47 . There is evidence that the C-terminal of the spike's cytoplasmic tail of SARS-CoV-2 is the key to retention of membrane-mediated spike in the endoplasmic reticulum-Golgi intermediate compartment (ERGIC) 48 .…”
Section: Cholesterol Affects Susceptibility By Influencing the Process Of Membrane Fusionmentioning
confidence: 99%
“…As defined earlier in results, the bulk cell membrane differs from the final budded virus membranes [32], though Env can cluster and associate with cholesterol even in the absence of supporting viral proteins such as Gag [31,33], and cell-presented Env retains enough functionality for cell-cell fusion assays [34][35][36]. Moreover, the survival of Env-presenting cells through KR13 treatment, in contrast to the shriveled and disordered morphology of KR13-treated virions [23], may be in part due to the more heterogeneous composition of cell membranes compared to the more defined and rigid virus membrane.…”
Section: Env-transfected Cells Function As Suitable Models For Evaluating Transformations Of Surface Env and Membranementioning
confidence: 65%
“…The known synthesis and trafficking pathways of Env account for no further processing or modification to the Env trimer between transport to cell surface and budding and assembly into free virions, and should leave Env in the same conformation [30,31]. While the cell membrane as a whole differs from the subset of regions that bud to form virus particles [32], there is evidence for the association of Env's cytoplasmic tail with cholesterol even without supporting viral proteins such as Gag [31,33], and the functionality of cell-cell fusion assays as alternative or complement to virus-cell assays indicates a sufficiently similar Env-membrane complex that retains fusion functionality [34][35][36].…”
Section: Ptt Kr13 Treatment Causes Transformation Of Cell-presented Env Resulting In Membrane Disruption Calcein Leakage and Specific Epimentioning
confidence: 99%
“…IFITMs have also been reported to restrict HIV-1 fusion and entry by modulation of the lipid bilayer ( 75 ). Biochemical studies have shown membrane fluidity influences HIV-1 Env mobility, stability, and conformation ( 76 , 77 ). Importantly, Env clustering and mobility in lipid membranes is dependent on the EnvCT.…”
Section: Discussionmentioning
confidence: 99%